Nipple-Areola Complex Necrosis after Nipple-Sparing Mastectomy with Immediate Autologous Breast Reconstruction - Jin-Woo Cho; Eul-Sik Yoon; Hi-Jin You; Hyon-Surk Kim; Byung-Il Lee; Seung-Ha Park (Archives of Plastic Surgery, 2015)
Background Autologous or implant-based breast reconstruction after nipple-sparing mastectomy is increasingly preferred worldwide as a breast cancer treatment option. However, postoperative nipple-areola complex (NAC) necrosis is the most significant complication of nipple-sparing mastectomy. The purpose of our study was to identify the risk factors for NAC necrosis, and to describe the use of our skin-banking technique as a solution. Methods We reviewed cases of immediate autologous breast reconstruction after nipple-sparing mastectomy at our institution between June 2005 and January 2014. The patients' data were reviewed and the risk of NAC necrosis was analyzed based on correlations between patient variables and NAC necrosis. Moreover, data pertaining to five high-risk patients who underwent the donor skin-banking procedure were included in the analysis. Results Eighty-five patients underwent immediate autologous breast reconstruction after nipple-sparing mastectomy during the study period. Partial or total NAC necrosis occurred in 36 patients (43.4%). Univariate analysis and binary regression modeling found that body mass index, smoking history, radiation therapy, and mastectomy volume were significantly associated with NAC necrosis. Of the 36 cases of NAC necrosis, 31 were resolved with dressing changes, debridement, or skin grafting. The other five high-risk patients underwent our prophylactic skin-banking technique during breast reconstruction surgery. Conclusions NAC necrosis is common in patients with multiple risk factors. The use of the skin-banking technique in immediate autologous breast reconstruction is an attractive option for high-risk patients. Banked skin can be used in such cases without requiring additional donor tissue, with good results in terms of aesthetic and reconstructive outcomes.